2011
DOI: 10.1111/j.1654-1103.2010.01243.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual and combined effects of disturbance and N addition on understorey vegetation in a subarctic mountain birch forest

Abstract: Questions: What are the effects of repeated disturbance and N‐fertilization on plant community structure in a mountain birch forest? What is the role of enhanced nutrient availability in recovery of understorey vegetation after repeated disturbance? How are responses of soil micro‐organisms to disturbance and N‐fertilization reflected in nutrient allocation patterns and recovery of understorey vegetation after disturbance? Location: Subarctic mountain birch forest, Finland. Methods: We conducted a fully fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Our study provides empirical evidence that geomorphological processes affect vegetation structure and biomass, with geomorphologic activity decreasing arctic-alpine plant biomass, probably through mechanical disturbance (Jonasson 1986;le Roux and Luoto 2014). The effect of geomorphology was the strongest for vegetation height, which may be explained by the fact that, generally, taller woody plants are more sensitive to disturbance and soil instability (Jonasson 1986;Haugland and Beatty 2005;Manninen et al 2011). For vegetation height the shared effects of geomorphology and topography are also strong (Fig.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Our study provides empirical evidence that geomorphological processes affect vegetation structure and biomass, with geomorphologic activity decreasing arctic-alpine plant biomass, probably through mechanical disturbance (Jonasson 1986;le Roux and Luoto 2014). The effect of geomorphology was the strongest for vegetation height, which may be explained by the fact that, generally, taller woody plants are more sensitive to disturbance and soil instability (Jonasson 1986;Haugland and Beatty 2005;Manninen et al 2011). For vegetation height the shared effects of geomorphology and topography are also strong (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…The effect of geomorphology was the strongest for vegetation height, which may be explained by the fact that, generally, taller woody plants are more sensitive to disturbance and soil instability (Jonasson ; Haugland and Beatty ; Manninen et al . ). For vegetation height the shared effects of geomorphology and topography are also strong (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…In northern boreal coniferous and mixed forests the dominance of E. nigrum is broken by recurrent fires (Zackrisson et al 1995 , 1996 ), which both remove above-ground plant parts and change soil conditions such as pH, humus layer thickness and nutrient availability. Field experimental studies have confirmed that severe disturbance is needed to break the dominance of E. nigrum , and that the effects of disturbance are enhanced by fertilization (Olofsson et al 2005 ; Manninen et al 2011 ). We have documented here that severe moth outbreaks effectively break the dominance of E. nigrum in a manner qualitatively similar to wild fires in coniferous forest, albeit on a much larger spatial scale.…”
Section: Discussionmentioning
confidence: 98%
“…E. hermaphroditum is unpalatable to most herbivores and relatively sensitive to disturbance (Tybirk et al., 2000). For example, clipping experiments have demonstrated its recovery to be much weaker compared with other species (Manninen et al., 2011), and that, when combined with fertilization, E. hermaphroditum could recover and out‐compete other plant species after a 50% biomass loss, but not after a complete biomass removal (Aerts, 2010). E. hermaphroditum may also decrease in abundance after winter conditions promoting pathogenic outbreaks (Olofsson et al., 2011), due to intense winter disturbance by rodents (Tuomi et al., 2019), and after moth outbreaks (Biuw et al., 2014).…”
Section: Discussionmentioning
confidence: 99%